(untitled) (Altre Modernità, 2024)
The object of this analysis is the study of the anomalous presence and use of one of the best known literary works of the Spanish postwar period in an ultra-contemporary Argentinian fiction, a case of non-declared palimpsestic communication that raises questions related to the topicality and universality of the classics, and, more interestingly, to the hypothesis of a trans-hemispheric dialogue between fictions that tackle collective crisis (post-war disruption in Laforet and economic exploitation in Morales). By commenting on the appropriation of major fragments of Carmen Laforet’s Nada in Bruno Morales’s Bolivia Construcciones, my purpose is to reestablish a pondered connection between the two works, denied at first by Morales/Di Nucci’s omissive opacity about his ’borrowing’, and, ultimately, to raise considerations on the existence and consistency of a trans-Hispanic literary language related to the socio-political traumas of the contemporary age.